OP0333 Discovery and validation of novel autoantigens in sjÖgren's syndrome with potential for subgrouping of disease. (15th June 2017) - Schulz-Knappe, PK; Budde, P; Zucht, H-D; Wirtz, D; Marquardt, K; Thomas, R; Witte, T; Schneider, M; Sivils, K; Rasmussen, A
Abstract : Background: Primary Sjögren's syndrome (pSS) is a common autoimmune disease with exocrine gland dysfunction and multi-organ involvement. With the growing interest in conducting clinical trials in pSS, there is a need for new biomarkers that can be used to diagnose pSS, identify clinical subsets of pSS, predict treatment outcome and assessment of disease activity. Activation of B-cells and dysregulation of the cytokine network plays a critical role in the pathophysiology of pSS. In the exocrine glands, elevated levels of cytokines, such as type I interferon (IFN), tumor necrosis factor alpha (TNF), interleukin 12 (IL-12) and B cell activating factor (BAFF) can be found. Dysregulated pathways of the innate and adaptive immune system lead to loss of tolerance and the production of organ-specific and non-specific autoantibodies. Current diagnostic criteria for pSS utilize autoantibodies directed to nuclear antigens (ANA), especially to SS-A/Ro (TRIM21, TROVE2) and La (SSB), but those are not specific, and can be identified as well in SLE and even in healthy volunteers. Several studies have shown that not all patients with pSS are tested positive for Ro and La autoantibodies, but suggested the existence of additional autoantibodies in pSS. This autoantibody burden is not well understood for the importance of disease progression, for its role in patient segmentation, or for response to treatments. Objectives: The discovery of novel autoantigens may provide a deeper understanding of mechanisms of actions for pSS drugs, and may be useful to stratify patients. Methods: The autoantibody reactivity pattern of pSS serum patients was analyzed using a Luminex bead-based antigen array (SeroTag) and 1, 600 selected human protein antigens from our hPEX protein library of 8, 000 recombinant proteins (1). We screened over 2, 000 serum samples from patients with autoimmune diseases as active controls targeting Sjögren's Syndrome (n=70), SLE (n=>500), SSc (n=>250), RA (n=>500), and over 1, 000 healthy individuals to confirm known and to discover novel autoantibodies. In a validation study, novel biomarker candidate antigens were evaluated using a cohort of 350 Patients with Sjögren's Syndrome. Results: Apart from clear confirmation the known benchmark autoantigens known for many years we have discovered a small set of additional, novel autoantibodies, which were detected in frequencies of 8 to >20% in pSS. Accumulation of autoantibody reactivities allows for a first subgroup definition of Sjögren's, and for clear segregation of SjS/SLE overlap syndrome patients. Conclusions: A set of novel autoantigens for diagnosis and subgroup definition in Sjögren's syndrome was discovered by high content screening using a Luminex bead-based array platform. Validation in additional, large patient cohorts is ongoing. References: Budde P et al. (2016). Lupus. (8):812–22. Disclosure of Interest: P. Schulz-Knappe Shareholder of: Protagen AG, P. Budde Employee of: Protagen AG, H.-D. Zucht: None declared, D. Wirtz Employee of: Protagen AG, K. Marquardt Employee of: Protagen AG, R. Thomas: None declared, T. Witte: None declared, M. Schneider Consultant for: Protagen AG, K. Sivils: None declared, A. Rasmussen: None declared